The role of bone radiotherapy during immune checkpoint inhibitors treatment of non-small-cell lung cancer: a single-institution experience - Ivan Facilissimo; Guido Natoli; Fabio Gaspari; Tiziana Comandone; Diego Bongiovanni; Paola Gollini; Claudia Provenza; Alessandro Comandone (Therapeutic Advances in Medical Oncology)
Background: Immune checkpoint inhibitors (ICIs) represent a keystone of cancer treatment, including non-small-cell lung cancer (NSCLC). Unfortunately, the efficacy of ICIs remains poor in patients with bone metastases from NSCLC. Recently, several case reports have suggested the clinical benefit of radiotherapy in advanced NSCLC patients. However, whether this positive effect is applicable during ICI treatment of NSCLC involving bones remains to be established. Methods: We retrospectively reviewed the records of patients with bone metastases who received ICIs as monotherapy (anti-PD1 or anti-programmed death-ligand 1) as well as in combination with platinum-based-chemotherapy (carboplatin or cisplatin). We next analyzed the presence or the absence of radiotherapy targeting bone metastases (RT) among these patients during immunotherapy. Results: A total of 40 patients were included in this study; among them, 10 (25%) received palliative RT for symptomatic bone metastases during cancer immunotherapy treatment with ICIs (RT group); the remaining 30 (75%) patients did not receive bone irradiation (Non-RT group). We observed that the RT group had a significantly longer overall survival (OS) than the Non-RT group, with a median survival of 16 months in the RT group versus 3 months in the Non-RT group (log-rank test p  < 0.048; hazard ratio (HR) for OS = 0.44; 95% confidence interval (CI): 0.18–1.00). Similar results were observed with respect to progression-free survival (PFS; log-rank test p  < 0.016; HR for PFS = 0.34; 95% CI: 0.15–1.00). Conclusion: Our results suggest that radiotherapy to bone metastases may improve ICIs efficacy in patients with bone metastatic NSCLC.